WILLIAM JAMES ON THE PRAGMATIC CONCEPTION OF TRUTH AND HUMAN KNOWLEDGE: A REFORMATIONAL REFLECTION - Jadi Sampurna Lima (STTRII, 2018)
At a glance, William James’ conception of truth in epistemology, especially in its critique of Modernism’s a-temporal, a-contextual, and absolutist conception of truth sounds very similar with a critique from Herman Dooyeweerd of the Reformational tradition. In this article, I would show what those similarities are and how the two systems are radically different. This research may be significant for Pragmatism is widely known and accepted in the late 20th century and well into the 21st century. Pragmatism is quite successful in grounding the elitist and abstract discourse of the academia to its daily contexts. KEYWORDS: James; Dooyeweerd; Truth; Pragmatism; Refomational Epistemology.